2022
DOI: 10.1002/jsfa.12252
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: a potential exogenous additive for the prevention of LPS‐induced duck ileitis by the alleviation of inflammation and oxidative stress

Abstract: BACKGROUND Lipopolysaccharides (LPS) are the main pathogenic substances in Gram‐negative bacteria. The aim of this study was to investigate the preventive effects of dietary curcumin (CUR) on LPS toxicity in the duck ileum. The duck diet was supplemented with CUR (0.5 g kg−1) for 28 days, while the birds were injected with LPS (0.5 mg kg−1 body weight per injection, administered as seven injections in the last week of the experimental period). RESULTS LPS significantly decreased the ileal villus‐to‐crypt ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In addition, the downregulation of Toll‐like receptor (TLR)/NLRP3/inducible nitric oxide synthase pathway is an innovative and safe strategy for treating patients with IBD [30] . Inhibition of TLR4, one LPS target, can reduce the expression of inflammatory factors including NF‐κB, NLRP3 and TNF‐α [31] . Previous data show that the molecular weight of polysaccharide ligands of TLR4 receptor is between 10~1000 kDa, which has high biological activities [32] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the downregulation of Toll‐like receptor (TLR)/NLRP3/inducible nitric oxide synthase pathway is an innovative and safe strategy for treating patients with IBD [30] . Inhibition of TLR4, one LPS target, can reduce the expression of inflammatory factors including NF‐κB, NLRP3 and TNF‐α [31] . Previous data show that the molecular weight of polysaccharide ligands of TLR4 receptor is between 10~1000 kDa, which has high biological activities [32] .…”
Section: Resultsmentioning
confidence: 99%
“…[30] Inhibition of TLR4, one LPS target, can reduce the expression of inflammatory factors including NF-kB, NLRP3 and TNF-α. [31] Previous data show that the molecular weight of polysaccharide ligands of TLR4 receptor is between 10~1000 kDa, which has high biological activities. [32] Current data indicated that the average molecular weight of PNP-20, -40, and -60 was less than 1000 kDa.…”
Section: Pnp-20 Ameliorated Intestinal Injury and Inflammatory Cells ...mentioning
confidence: 99%
“…On the other hand, lipopolysaccharides (LPSs), components responsible for the pathological process of contamination induced by Gram-negative bacteria, can cause morphological damage to the ileum, lung injury, inflammation, and oxidative stress in poultry. The addition of 500 mg/kg of curcumin to the diet could ameliorate these symptoms in the lungs and ileitis of ducks through the signaling pathways of Nrf2-ARE, NF-κB, and TLR/NF-κB in an orderly manner [ 87 , 88 ]. Furthermore, curcumin has shown effectiveness against coccidiosis caused by Eimeria species.…”
Section: Curcumin In Stress Management Of Avianmentioning
confidence: 99%
“…We propose that the curcumin-based fluorescent sensor may have low cytotoxicity. [33][34][35] Moreover, curcumin and its derivatives have a large conjugate structure, which could enhance the π electron delocalization. The curcumin and its derivatives are better to be emitted to generate outstanding long-wavelength fluorescence.…”
Section: Introductionmentioning
confidence: 99%